Design and assessment of effective multimedia-based courseware for student quantitative data analysis - Yassin, Abdulnassir; Bashir, Ashadi; Surjono, Herman Dwi; Afdal, Zul; Novianto, Victor (Institute of Advanced Engineering and Science, 2025)
The rapidly evolving technological trends are transforming higher education. This study focused on designing and evaluating the effectiveness of multimedia-based courseware in improving students’ data analysis at Islamic University in Uganda. The objectives were: i) to create interactive multimedia courseware (IMC) to enhance students’ quantitative data analysis skills; ii) to evaluate the suitability of IMC’s content, interactivity, user interface, and design; and iii) to profile students’ perceived benefits of using the IMC to learn quantitative data analysis. A descriptive survey involving 160 education undergraduate finalists, selected through random and consensus sampling, was conducted. Data was collected through a self-report survey instrument with high validity (content validity index=0.886) and reliability (Cronbach alpha=0.878). The IMC development followed the analysis, design, development, implementation, and evaluation (ADDIE) model and Gagne’s learning events. Results indicated that the IMC content (mean=3.90, SD=0.94), interactivity (mean=4.10, SD=0.79), user interface (mean=4.04, SD=0.82), and screen design (mean=4.05, SD=0.87) were highly appropriate. Students perceived IMC as effective in enhancing their data analysis skills (mean=3.86, SD=0.92). The findings suggest that IMC can significantly improve students’ quantitative analysis abilities. However, recommending further studies on the impact of IMC on students’ quantitative data analysis skills comprehensively in a multidisciplinary manner, to potentially revolutionize learning.